DETERMINAN PRAKTIK MEROKOK KEPALA KELUARGA DI KELUHARAN CIBADUYUT KOTA BANDUNG - Junisa, Nurfita Ainaiyah; Abdurrahmat, Asep Suryana; Maywati, Sri (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2023)
Smoking is a habit of smoking cigarettes carried out by society and is an unavoidable necessity for someone who has a tendency towards smoking. Based on 2018 Basic Health Research data, the prevalence of smoking in Bandung City exceeds the provincial figure, namely 34.04%. The lowest indicator of not smoking in the house in the city of Bandung is in Cibaduyut Village with a prevalence of 8.63%, so research was conducted on the behavioral determinants that influence the head of the family to practice smoking. The method used in this research is a quantitative method with a descriptive approach and the research design used is Cross Sectional. The research population of heads of families living in Cibaduyut sub-district was 2,716 heads of families. The sample of 249 heads of families was selected using a proportional random sampling technique, namely. The research instrument was a questionnaire and the data was analyzed by the chi square test at an alpha significance level of 0.05. The results of the research show that there were a relationship between the variables of attitudes include beliefs, values, traditions, affordability of cigarettes, and social environment with the smoking practices of family heads in Cibaduyut Village, Bandung City. Meanwhile, for the variables of knowledge and exposure to cigarette advertising, there was no significant relationship. Society is expected to start changing the paradigm that can influence smoking practices.